Takhrij Hadis dan Metode-Metodenya - Azan Sagala (Yayasan Rahmat Islamiyah, 2021)
This study aims to analyze the takhrij hadith and its various methods. This research uses a qualitative approach based on library research or literature study. This study uses documentation data collection techniques, meaning the techniques of collecting data based on written documents on the research topic. This document can be in the form of books, journals, traditions of the Prophet Muhammad, and so on. The results of the study explain that Takhrij hadith is tracing a hadith to its origin in the Jami, Sunan, and Musnad books then if necessary mentioning the quality of the hadith whether it is authentic, Hasan or doif. The benefits of takhrij hadith itself are providing information on whether the hadith is authentic, hasan or daif, makes it easy for people who want to practice it after knowing that the hadith is valid (acceptable), and strengthens the belief that the hadith really comes from the Prophet Muhammad. Keywords: Takhrij Hadis, Shahih, Hasan, Maudhu’